Necesidad de reformar la ley de educación de intercultural bilingüe, a fin de regular la situación de los estudiantes que por razones de carácter religioso se ven impedidos de cumplir con obligaciones de carácter cívico en sus instituciones educativas - Ayovi Cuellar., Ángel Superman (2014)
This legal research falls within the academic problems of the Organic Law of Education, meets the requirements laid down in Regulation Academic Board of the National University of Loja , which regulates the legal relevance of the research study aspects inherent in the materials Positive law, to qualify for the law degree. In sociological aims to demonstrate the need for effective protection of the state towards students of different educational levels , they suffer marginalization and discrimination by educational authorities, teachers and by the same partners that their parents to have a common religion that is different Catholic , for this reason and because of their beliefs can not meet certain obligations of a civil and especially, suffer retaliation and sanctions that affect their educational development. The problem has to be social and legal significance for investigation, seeking to solve the problem posed for the benefit of students of different educational levels. This discrimination and marginalization by religious causes , in which the student has no responsibility because it is the responsibility of parents, is a legal problem because they are behavior that undermine the inherent rights of freedom of conscience of individuals guaranteed in the Constitution of the Republic and in international conventions, is a serious problem internally in the educational institutions themselves, which on one hand are at the refusal of these students meet events and commemorations civic, so they are punished. Discrimination and marginalization students by subject of religious belief in our environment have increased dramatically, there are frequent cases where students are expelled or estranged from the educational institutions for refusing to comply with these particular civic obligations , parades, civic events , pledge of Allegiance and other expulsions and sanctions that harm the process of educational training, also creating frustration and psychological damage to the individual student. This research addresses this problem from a legal standpoint, as constituting acts against freedom of conscience and thought of students affect their personality and hinder their emotional and moral development.